Aplikasi Teori Katharine Kolbaca Pada Kasus Kanker Kolon Pasca Laparatomi Dengan Musik - monika rini puspitasari; Agung Waluyo (STIKES ADVAITA MEDIKA TABANAN, 2021)
Colorectal cancer is a malignancy that originates in the tissue of the colon and is the second leading cause of death worldwide. Laparatomy is one of the most commonly performed types of surgery. Pain can appear after the laparotomy due to the severity of body tissues. Writing this case study to identify the use of music therapy in interventions to reduce pain after laparotomy surgery in the case of Mr.S. Assessment of the pain scale uses the NRS (Numeric Rate Scale) while the patient's condition is through observation and intervention. The results of the observation found data if Mr.S said that the pain during activities was on the part of the laparotomy incision in the abdomen with an NRS 6 scale. The main nursing diagnosis in Mr. S's case was pain. The intervention given uses an approach based on nursing theoryKatharine Kolbaca is the theory of comfort. Management to manage pain can be done with pharmacological and non-pharmacological therapies. The non-pharmacological therapy given to Mr. S. was in the form of music therapy that was selected independently by Mr. S. and carried out for 4 sessions in 2 days. The findings of this study were that the administration of music therapy had the effect of reducing the pain scale compared to the beginning of the assessment.